2013
DOI: 10.2337/db12-0491
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Is a Novel Regulator of Contraction-Stimulated Glucose Uptake in Skeletal Muscle

Abstract: In skeletal muscle, the actin cytoskeleton-regulating GTPase, Rac1, is necessary for insulin-dependent GLUT4 translocation. Muscle contraction increases glucose transport and represents an alternative signaling pathway to insulin. Whether Rac1 is activated by muscle contraction and regulates contraction-induced glucose uptake is unknown. Therefore, we studied the effects of in vivo exercise and ex vivo muscle contractions on Rac1 signaling and its regulatory role in glucose uptake in mice and humans. Muscle Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
221
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(246 citation statements)
references
References 49 publications
18
221
4
3
Order By: Relevance
“…For instance, a GEF other than FLJ00068 may be responsible for contraction-stimulated Rac1 activation. Additionally, it was reported that Rac1 activation in response to contraction is not mediated by AMPK 71 . This may be an unexpected result, taking into consideration that AMPK has been implicated in contraction-dependent glucose uptake as described above, and AMPK can stimulate Rac1 (see below).…”
Section: Role Of Rac1 In Contraction-stimulated Glucose Uptakementioning
confidence: 84%
See 1 more Smart Citation
“…For instance, a GEF other than FLJ00068 may be responsible for contraction-stimulated Rac1 activation. Additionally, it was reported that Rac1 activation in response to contraction is not mediated by AMPK 71 . This may be an unexpected result, taking into consideration that AMPK has been implicated in contraction-dependent glucose uptake as described above, and AMPK can stimulate Rac1 (see below).…”
Section: Role Of Rac1 In Contraction-stimulated Glucose Uptakementioning
confidence: 84%
“…A pivotal role of Rac1 in contraction-stimulated glucose uptake in skeletal muscle has been clarified by using muscle-specific rac1 knockout mice 71 . The activation of Rac1 was observed after exercise in both mice and humans, and contraction-stimulated glucose uptake was abrogated in rac1 knockout mouse skeletal muscle.…”
Section: Role Of Rac1 In Contraction-stimulated Glucose Uptakementioning
confidence: 99%
“…The paramount intracellular signal triggered by changes in the AMP/ATP ratio is activation of the AMP-activated protein kinase (AMPK). Signals triggered by mechanical stretch include the small G protein Rac1 and its downstream effector kinases PAK1/2 (8,42). These pathways may also intersect one another to affect glucose uptake, as exemplified by the activation of AMPK by CaMKK (22,49).…”
mentioning
confidence: 99%
“…Consistent with this notion, Nox2 knockout mice have higher baseline levels of plasma glucose and insulin compared to wild type animals [161]. Muscle contraction and stretch stimulate glucose transport in a ROS-dependent manner [176, 177], and recent studies have indicated that Rac1 is required for contraction- and stretch-stimulated glucose uptake in skeletal muscle [76, 178]. These findings suggest Nox2-derived ROS as potential mediators of skeletal muscle glucose transport.…”
Section: Nox and Skeletal Muscle Biology In Health And Diseasementioning
confidence: 84%